Preparation and Characterization of Al2O3/h-BN Composite Coatings by Atmospheric Plasma Spraying (APS) - Yifeng Guo; Lingxiao Lan; Boying Qin; Xinghua Liang; Yujiang Wang; Yu Wang; Zhikun Chen (Crystals)
To improve the adhesion strength of polymer functional films, corona treatment is required. Corona rollers are key components for corona treatment, which are used in high-voltage electric fields for a long time. In this work, in order to improve electrical insulation, arc resistance, wear resistance, and chemical stability, a coating is usually sprayed on the surface of the corona roller. Al2O3/h-BN composite coatings are prepared on the surface substrate of a corona roller (20 steel) by atmospheric plasma spraying (APS) technology. Scanning Electron Microscope (SEM) and X-ray diffraction (XRD) analysis showed that the Al2O3/h-BN composite coating had a layered structure and compactness. Two kinds of Al2O3/h-BN composite coatings are prepared under different APS process parameters; the porosities of A coating and B coating are 6.04% and 4.75%, the microhardnesses are 781 ± 0.5 Hv and 840.5 ± 0.5 Hv, and the adhesion strengths are 22.0 MPa and 22.3 MPa, respectively. The A and B volume resistivity of the coatings are 9.29 × 1010 Ω·cm and 3.55 × 1010 Ω·cm, respectively. The volume resistivity and porosity of the coatings are negatively correlated, and they decrease with the increase in spraying current. But for both coatings, volume resistivity is greater than 1 × 1010 Ω cm. These results indicate that the Al2O3/h-BN composite coatings, as a new type of electrode roller coating, satisfy the use requirement. Al2O3/h-BN composite coatings can become the potential for ceramic coatings that have good mechanics and insulation performance.